Unpacking China's industrial policy and its implications for Europe - Alicia García Herrero; Robin Schindowski (Bruegel, 2024)
China is often credited with a successful application of industrial policy. One important particularity of China's industrial policy is that it aims at levelling the playing field between the state economy and the private economy in access to finance, yet within a framework of strategic goals. This aim is not relevant for market economies, such as those of the European Union, but only for those where state enterprises are clearly privileged. Notwithstanding the difficulties in making valid comparisons, our analysis of how China conducts industrial policy in a variety of sectors points to success in some sectors but not all. More importantly, productivity growth in China has already been declining for two decades. Given the very large resources that China has put into industrial policy, with subsidies being only one part, it is surprising that success is not more evident. This relates partly to factors including cronyism and regional protectionism. While the former might be less relevant for the EU given the different institutional background, the latter certainly is relevant since the EU faces the potential consequences of member country-level industrial policy for its single market. A lesson from China seems to come from the sectoral focus, with a long-term and economic-security mindset. The EU is far from this, but it is in the process of linking economic security to industrial policy. Finally, responding to China's industrial policy involves diverse investigations and challenges in measuring subsidies accurately. Understanding China's very diverse and complex approach to helping companies achieve the government's industrial policy goals is crucial for anticipating the consequences of China's actions. These could be positive, such as cheaper imports of green technology, or negative, such as Chinese overcapacity spilling over to the EU single market.
Keywords: 330